Evaluasi Resiko pada Konstruksi Proyek Pembangunan Gedung Kantor Pengadilan Tata Usaha Negara Gorontalo - Fikriyanto Ome; Moh. Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
The construction of the Gorontalo State Administrative Court Office Building, initiated in August 2023 and scheduled for completion in June 2024, presents significant risks due to its fluctuating nature, extensive workload, and constrained time and budget. These factors critically affect productivity, quality, and costs. This study aims to evaluate project risks and identify dominant risks using the Probability Impact Matrix (PIM) method. Data were collected through questionnaires distributed to 30 respondents and analyzed using SPSS software to ensure validity and reliability. The analysis identified 26 valid risks, with three dominant risks emerging as high-priority concerns: material price increases (risk score of 20), material availability issues (risk score of 16), and delays in material procurement (risk score of 16). These risks fall within the high-level category and require immediate mitigation to minimize their adverse impact on project timelines and financial stability. Effective risk management strategies, including supplier diversification, long-term procurement agreements, and inventory control, are essential to mitigating these risks. Additionally, proactive planning and continuous monitoring are necessary to ensure project completion within the allocated time and budget. The findings of this study provide valuable insights for project managers and stakeholders in addressing critical risk factors in high-risk construction projects. Future research should explore advanced risk assessment models and mitigation techniques to enhance construction project resilience.